Rapidly progressive Guillain–Barré syndrome following amitriptyline overdose and severe Klebsiella pneumoniae infection: A case report and literature review - Zhang, Boyu; Duan, Liwei; Ma, Linhao; Cai, Qingqing; Wu, Hao; Chang, Liang; Li, Wenfang; Lin, Zhaofen (Frontiers in Medicine, 2022)
Guillain-Barré syndrome (GBS) is a potentially life-threatening post-infectious autoimmune disease characterized by rapidly progressive symmetrical weakness of the extremities. Here, we report a case of GBS associated with drug poisoning complicated by Klebsiella pneumoniae infection. A 38-year-old woman was admitted to the ICU with amitriptyline overdose, coma, Klebsiella pneumoniae infection, and septic shock. Thirteen days later, she was diagnosed with GBS based on acute muscle pain, flaccid paralysis, hyporeflexia, reduced amplitude of compound muscle action potentials, and albuminocytologic dissociation in the cerebrospinal fluid. GBS rarely occurs after drug overdose and septic shock, and this is the first report of rapidly progressive GBS following amitriptyline overdose and severe Klebsiella pneumoniae infection.